Współczesna antropologia a kantowska krytyka metafizyki - Stanguennec, André (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1995)
The author of the paper analyses different varieties of Kantianism – sometimes more true to the spirit than to the letter of Kant’s – which appear in the 20th century anthropology. Thus he allows us to see that the thought which looks back to Kant is able to remove "complexes" and overcome the "inner contradictions" of modern anthropology.